Spatiotemporal variations of surface and groundwater interactions under climate and land use land cover change scenarios - Loukika, Kotapati Narayana; Keesara, Venkata Reddy; Buri, Eswar Sai; Sridhar, Venkataramana (Frontiers in Water, 2025)
The behaviour of water between the surface and subsurface is a dynamic and intricate process, involving a complex interplay between surface water and groundwater. This interaction is vital for supporting ecosystems, providing water supplies, and ensuring the sustainable use of water resources. Disruptions in these interactions, such as over-extraction, reduced streamflow, and the impacts of climate change, contribute to water scarcity. An integrated management of surface and groundwater resources is crucial for addressing these challenges and ensuring the long-term availability and sustainability of water supplies. In this study, the spatiotemporal variations of surface and groundwater interactions were analysed using integrated SWAT and MODFLOW model using QSWATMOD plugin in QGIS software. The surface and groundwater interactions were analysed for future periods under climate and land use land cover (LULC) change scenarios. Pre-monsoon, monsoon, post-monsoon kharif, and post-monsoon rabi seasons are considered for analysing the surface and groundwater interactions. The future LULCs are projected using the DynaCLUE model for three user-defined scenarios such as past trend (scenario 1), drastic change in built-up and barren land (scenario 2), and restricted agricultural land (scenario 3). For projecting the interactions under both changing climate and LULC, LULC scenario 1 was used for near-future period, LULC scenario 2 for mid-future period, and LULC scenario 3 for far future period. Under the climate change scenario, the maximum groundwater recharge under SSP5-8.5 scenario is observed to be 20,805 m3/day in the near future, and the maximum discharge under SSP2-4.5 scenario is observed as 9,035 m3/day in the mid-future period. In both climate change and combined scenarios (both climate and user-defined LULC), there was a greater recharge of groundwater during the monsoon season relative to other seasons, while there was a greater discharge of groundwater during the post-monsoon rabi season. In the combined scenarios, the maximum discharge was under SSP5-8.5 with 15,009 m3/day in the mid-future, and the groundwater recharge was greater in the near future period under SSP3-7.0 with 19,556 m3/day. The groundwater–surface water interactions were analysed in four seasons, out of which monsoon season had the maximum recharge and groundwater discharge was more in the post-monsoon rabi season. The results found in this study’ can be used to plan and develop short-and long-term integrated surface and groundwater management strategies of the basin under changing climate and LULC.